Role of Inhibitory Check Point (CTLA-4) in Iraqi Women with Breast Cancer - Hamed Hussein Ali Al- Saadi; Hazima Mossa Al-Abassi; Mohammed Mahdi Jawad (Institute of Medico-legal Publications Pvt Ltd, 2021)
Breast cancer is the most important and frequently diagnosed cancer among women worldwide. The CTLA4 is a member of Immunoglobulin super family and binds to the CD80 and CD86 co-stimulatory molecules.(binds to CD80/86 on APCs with a higher affinity than CD28, thereby inhibiting co-stimulatory signals.CTLA-4 (Gene ID:1493, MIM number: 123890) is a new member of the immunoglobulin super family known as insulin-dependent diabetes mellitus 12 (IDDM 12) ,and cluster of differentiation 152 (CD152).The CTLA-4 protein consists of a 37 amino acid leader peptide, an extracellular immunoglobulin (Ig) V like domain or the ligand-binding domain (116 amino acid), a hydrophobic trans membrane region (37 amino acid), and a cytoplasmic domain. The aim of the present study of the association of CTLA-4 serum level and polymorphism with breast cancer in Iraqi women suffers from breast cancer. Materials and Methods: peripheral Blood samples were collected from 45 Iraqi patients women diagnosed with breast cancer patient, and 45 healthy women were matched with patients as a control. ELISA technique has been used to determine the serum level of sCTLA-4.The polymerase chain reaction (PCR) performed on 45 patients and 45 control, to determine the genetic variation in the +49 exon 1 region of CTLA-4 gene. Results: the serum level of understudying groups recorded an non-significant difference increasing in the serum level of CTLA-4 under (p>0.05). in mean ± SE (3.17 ± 0.82 ng/ml) patients as compared to control (2.72 ± 0.29 ng/ml) under (p>0.05). Genetic polymorphism of CTLA.4 gene (rs231775) which illustrated the distribution of genotypes of CTLA.4 in patients and control. The heterozygous genotype AG recorded high frequency in patients (35.56%) than control (0.00%) with a highly significant difference under (P<0.05). Homozygote genotype AA recorded high frequency in control (95.56%) than patients (64.44) and has a highly significant difference, and the homozygous genotype GG frequency (0.00%) was non- significant in patients compared to control (4.44%). The allele frequency for allele A was (0.82%) in patients compared with control (0.96%) while for the frequency of allele G was (0.18%) in patients compared with control (0.04%) with a significant difference. Conclusion: elevation of serum concentration of sCTLA-4 could consider as a clinical biomarker for prognosis breast cancer. There are some difference noticed in CTLA-4 gene with SNP (rs231775A/G) which showed a significant differences between patients and control, A allele of SNP (rs231775A/G) may have role to prevent the risk of breast cancer in Iraqi females, while allele G has an etiological fraction.